Increased nuclear suppressor of cytokine signaling 1 in asthmatic bronchial epithelium suppresses rhinovirus induction of innate interferons - Gielen, Vera; Sykes, Annemarie; Zhu, Jie; Chan, Brian; Macintyre, Jonathan; Regamey, Nicolas; Kieninger, Elisabeth; Gupta, Atul; Shoemark, Amelia; Bossley, Cara; Davies, Jane; Saglani, Sejal; et al. (Journal of allergy and clinical immunology, 2015)
Rhinovirus infections are the dominant cause of asthma exacerbations, and deficient virus induction of IFN-α/β/λ in asthmatic patients is important in asthma exacerbation pathogenesis. Mechanisms causing this interferon deficiency in asthmatic patients are unknown. We sought to investigate the expression of suppressor of cytokine signaling (SOCS) 1 in tissues from asthmatic patients and its possible role in impaired virus-induced interferon induction in these patients. We assessed SOCS1 mRNA and protein levels in vitro, bronchial biopsy specimens, and mice. The role of SOCS1 was inferred by proof-of-concept studies using overexpression with reporter genes and SOCS1-deficient mice. A nuclear role of SOCS1 was shown by using bronchial biopsy staining, overexpression of mutant SOCS1 constructs, and confocal microscopy. SOCS1 levels were also correlated with asthma-related clinical outcomes. We report induction of SOCS1 in bronchial epithelial cells (BECs) by asthma exacerbation–related cytokines and by rhinovirus infection in vitro. We found that SOCS1 was increased in vivo in bronchial epithelium and related to asthma severity. SOCS1 expression was also increased in primary BECs from asthmatic patients ex vivo and was related to interferon deficiency and increased viral replication. In primary human epithelium, mouse lung macrophages, and SOCS1-deficient mice, SOCS1 suppressed rhinovirus induction of interferons. Suppression of virus-induced interferon levels was dependent on SOCS1 nuclear translocation but independent of proteasomal degradation of transcription factors. Nuclear SOCS1 levels were also increased in BECs from asthmatic patients. We describe a novel mechanism explaining interferon deficiency in asthmatic patients through a novel nuclear function of SOCS1 and identify SOCS1 as an important therapeutic target for asthma exacerbations.